AN INNOVATIVE SERVICE FOR SUSTAINABILITY IN BRAZIL: THE PANTANAL BRAZIL WEB SITE CASE - de Azevedo, Beatriz Marcondes; Erdmann, Rolf Hermann; Campos, Fred Leite Siqueira; Graeff, Maria Augusta (European Scientific Journal, ESJ, 2014)
The Pantanal BRAZIL Â® Portal is a website aims to create sustainable value and shared in the process of interaction between people and organizations through information, products and services generated by the states the Pantanal: Mato Grosso and Mato Grosso do Sul. It a service organization that operates in the sector of Information Technology offering a platform for digital content distribution aimed at promoting commercial development, cultural and social development in the Pantanal region. Thus the Portal Pantanal Brazil wants to seize opportunities to encourage various sectors intensifying their shared value. Given the above, this article aims to propose a critical reflection on the process of design and operation of an innovative service by reporting the steps followed from the moment of conception until the moment the idea of his offering to the market. Furthermore, we evaluated the performance of the new service with the purpose of identifying your strengths and opportunities for improvement. Thus, in methodological terms, this is an exploratorydescriptive, in the form of a case study. Data were collected from the Google Analytics to a sample of Internet users who accessed the portal for the four years that it is operating. The results indicate that in terms of resources, the portal is considered a platform for synergistic action, acting as a channel for interactivity between the Region of Pantanal and the national and international market.